2017
DOI: 10.17344/acsi.2017.3544
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Student Learning during Experimental Work in Primary School

Abstract: The aim of the research was to optimize the effectiveness of student learning based on experimental work in chemistry classes in Slovenian primary schools. To obtain evidence about how experimental work is implemented during regular chemistry classes, experimental work was videotaped during 19 units of chemistry lessons at 12 Slovenian primary schools from the pool of randomly selected schools. Altogether 332 eight-grade students were involved in the investigation, with an average age of 14.2 years. Students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
11
1
1
Order By: Relevance
“…Killian (2018) emphasizes that teacher-led practice requires that students engage first in explicit instruction, followed by guided practice, and ultimately move toward independence. However, as this study did not find independence to be a statistically significant predictor of academic achievement, it can be inferred that teachers may be confusing the concept of independent learning routines for students choosing how, when and what they learn (characteristics of what this study established to be student-centred learning routines), without clear objectives (Logar et al, 2018). Alternatively, when teachers design and lead learning routines (Adler et al, 2018) with clear expectations and objectives (Dishon-Berkovits, 2014;Logar et al, 2018), student motivation and academic achievement may be enhanced.…”
Section: • •contrasting
confidence: 58%
See 1 more Smart Citation
“…Killian (2018) emphasizes that teacher-led practice requires that students engage first in explicit instruction, followed by guided practice, and ultimately move toward independence. However, as this study did not find independence to be a statistically significant predictor of academic achievement, it can be inferred that teachers may be confusing the concept of independent learning routines for students choosing how, when and what they learn (characteristics of what this study established to be student-centred learning routines), without clear objectives (Logar et al, 2018). Alternatively, when teachers design and lead learning routines (Adler et al, 2018) with clear expectations and objectives (Dishon-Berkovits, 2014;Logar et al, 2018), student motivation and academic achievement may be enhanced.…”
Section: • •contrasting
confidence: 58%
“…Perhaps concerningly, findings explained that only half of educators planned in this way, compromising the effectiveness of investigative learning on academic achievement. It can be suggested that despite the potential for investigative learning to increase student motivation, this alone; in the absence of teacher instruction; may not be not enough to support academic achievement (Logar et al, 2018). These findings echo Dishon-Berkovits ( 2014) and Adler et al's (2018) acknowledgement of the fundamental role of the teacher in intentionally leading the learning, with clear objectives and a strong basis of content knowledge.…”
Section: Investigationmentioning
confidence: 79%
“…Therefore, sustained efforts should be focused on productive school-university collaboration, but also to raising of the awareness for the need of in-service chemistry teachers' sustainable education in their subject area in relation to recent findings from chemical education research, e.g. studying the impact of different experimental methods in chemistry teaching on school practice, 24,25 studying the impact of the online knowledge assessment system on students' knowledge, 26 the development of concept maps as learning materials to foster students' meaningful learning of organic reactions. 27 …”
Section: Resultsmentioning
confidence: 99%
“…However, most of the interviewed students stated that they preferred conducting experiments themselves rather than observing a teacher's demonstration. A followup study (Logar, Peklaj, & Ferk Savec, 2017) aimed to provide further details related to the effectiveness of student learning based on experimental work in primary schools. The results identified eight factors that seem to be the most important for effective student learning, of which four factors are part of the teacher's preparation for experimental work, and the other four are related to the thoughtful implementation of experimental work in the classroom.…”
Section: Experimental Workmentioning
confidence: 99%